Pengaruh Beauty Influencer, Viral Marketing Dan Online Customer Review Terhadap Keputusan Pembelian ProdukSkintific di Aceh Barat. - Sri Wahyuni; Cut Mega Putri (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to identify and analyze the influence of Beauty Influencers, Viral Marketing, and Online Customer Reviews on purchasing decisions for Skintific products. The sample selection in this study used a non-probability sampling method with a purposive sampling technique. Using the Slovin formula, the required sample size was calculated as 98.5; therefore, 100 respondents were considered sufficient to represent the study. In collecting data, the researcher used primary data sources through questionnaires distributed to respondents. The research data were analyzed using multiple linear regression analysis, coefficient of determination analysis, t-test, and F-test. The results of this study indicate that Beauty Influencers, Viral Marketing, and Online Customer Reviews have a positive and significant effect on purchasing decisions for Skintific products